Exploring definitions and experiences of loneliness: Insights from interviews with children and early adolescents in Italy - Brunetti, Matilde; Sette, Stefania; Galanaki, Evangelia P.; De Marco, Lavignia; Laghi, Fiorenzo; Longobardi, Emiddia; Coplan, Robert J. (Social Development, 2025)
Loneliness represents a negative feeling that arises when individuals perceive a discrepancy between actual and desired social relationships. The present study explored the meanings and personal experiences of loneliness in children and early adolescents in Italy. Participants included 139 children and early adolescents aged 8–14 years (M = 10.76 years, SD = 1.71; 80 girls, 57.6%) who completed a semi-structured interview online. Different dimensions emerged from the coding process, providing evidence of the multidimensional nature of loneliness, defined and experienced through different dimensions (e.g., cognitive, emotional, and regarding interpersonal context). Results from descriptive analyses (i.e., frequencies and percentages) showed that most of the participants defined loneliness in terms of physical separation from others. Also, participants discussed loneliness in relation to both their family and peers. Some children and adolescents expressed experiencing loneliness voluntarily. Children and early adolescents reported to feel sadness, anger and other emotions as boredom, happiness, and fear in associations with loneliness. Finally, we examined gender and grade differences between the dimensions with a series of chisquare tests and ANOVAs. Results revealed that primary school children and boys defined and experienced loneliness using the physical separation dimension. Middle school children defined loneliness using the cognitive dimension more frequently. Overall, the present study offers a richer understanding of the meanings and experiences of loneliness in youth and highlights the importance of considering developmental, gender, and cultural factors when studying loneliness.